The confidence of undergraduate dental students when carrying out prosthodontic treatment and their perception of the quality of prosthodontic education. (11th May 2017) - Puryer, J.; Woods, K.; Terry, J.; Sandy, J.; Ireland, A. J.
Abstract: Introduction: Despite the falling number of edentulous patients within the UK, there is still a large demand for the provision of removable prostheses. On qualification, dentists should have the knowledge and skills to provide these prostheses, but previous studies have shown that final‐year dental undergraduate confidence in treating denture patients is lacking. Aim: To explore undergraduate dental student confidence whilst carrying out prosthodontic treatment, and to explore their perceptions of the quality of their prosthodontic education. Method: An anonymous questionnaire was distributed to all (n=203) dental undergraduates in Years 3 to 5 at the University of Bristol. The questionnaire utilised a range of data collection methods including confidence interval ranked responses and qualitative measures. The data were analysed using SPSS. Results: The response rate was 51%. Undergraduate perception of confidence increased throughout the years of study ( P <.001). There was also an increase in the number of partial and complete denture cases treated as students progressed through the course ( P <.001). Overall, students were satisfied with their prosthodontic teaching, although students thought that too much time was allocated to laboratory teaching, and that increasing their clinical experience would be most beneficial in increasing their confidence levels. Conclusion: Student confidence in carrying out prosthetic treatment increased as students progressed through the course, and confidence levels would be increased further with increased clinical experience.